Embryogenesis of the nasal cavity - Yemelyanenko , N.R.; Proniaiev , D.V. (Морфологія / Morphologia / Morfologìâ, 2025)
Introduction. The results of numerous scientific studies indicate that embryological studies of the features of the laying and development of the nasal septum would shed light on the main phylogenetic features of the formation of the nasal septum and the possible evolutionary expediency of the development of certain types and degrees of nasal septum curvatures. Purpose of the study: to investigate the features of the laying and embryonic development of the human nasal septum. Methods. The studies were performed on human embryo preparations using the methods of microscopic examination of serial histological sections and the manufacture of plastic reconstruction. Results. At the 4th week of intrauterine development, the oral fossa is determined, which is limited above by the unpaired frontal process, below by the cardiac protrusion and laterally by the maxillary processes. Its posterior border is formed by the maxillary arch. Down and to the sides of the frontal tubercle, epithelial cells are compactly arranged, forming two thickened plates, represented by 4-5-row cylindrical epithelium. Along the periphery of the plates, epithelial cells protrude slightly above the level of the ectoderm, forming an elevation. In the area of ​​the middle part of the indicated epithelial thickenings in embryos 6.0 mm long, a slight indentation of the epithelium into the underlying mesenchyme occurs - this is the initial stage of the laying of nasal (olfactory) placodes. Slightly dorsal and lateral to the olfactory placodes is the second thickening of the epithelium, consisting of cylindrical cells, the nuclei of which form 5-6 rows, this thickening indents into the underlying mesenchyme and is the rudiment of lens placodes. The study of plastic reconstructions of the nasal region of embryos 13.5 mm long showed that both halves of the primary nasal cavity have a curved shape - directed first dorsally, and then somewhat caudally (towards the primary oral cavity) and open near its side walls. The primary nasal cavity is separated from the primary oral cavity by the primary palate. Conclusions: 1. The rudiment of the palatine process in the form of a small protrusion on the side wall of the primary oral cavity appears in embryos 18.0 mm long. 2. Both halves of the primary nasal cavity have a curved shape - directed first dorsally, and then somewhat caudally (towards the primary oral cavity) and open near its side walls. 3. The initial stage of laying nasal (olfactory) placodes occurs in embryos 6.0 long along the periphery of the plates, epithelial cells protrude above the level of the ectoderm, forming an elevation in the form of indentation of the epithelium into the underlying mesenchyme of the middle part of the indicated thickenings.